The Features of Extrahepatic Collateral Arteries Related to Hepatic Artery Occlusion and Benefits in the Transarterial Management of Liver Tumors - Lin Yang; Xiao Ming Zhang; Yong Jun Ren; Nan Dong Miao; Xiao Hua Huang; Guo Li Dong (Radiology Research and Practice)
Purpose. To investigate the extrahepatic collateral arteries related to hepatic artery occlusion (HAO) and to determine its benefits in the transarterial management of liver tumors. Methods and Findings. Eleven patients (7 hepatocellular carcinomas, 3 liver metastases, and 1 with hemangioma) with HAO confirmed with digital subtraction angiography (DSA) were admitted to our hospital. Of the 11 patients, 7 were men and 4 were women, with an average age of 41.5 ± 15.5 years (range: 29 to 70 years). DSA was performed to evaluate the collateral routes to the liver. In the 11 patients with HAO, DSA showed complete occlusion of the common hepatic artery in 9 patients and the proper hepatic artery (PHA) in 2 patients. Extrahepatic collateral arteries supplying the liver were readily evident. The collateral arteries originated from the superior mesenteric artery (SMA) in 8 patients, from the gastroduodenal artery in 2 patients, and from the left gastric artery (LGA) in 1 patient. Transcatheter treatment was successfully performed via the collateral artery in all patients except the one who had hemangioma. Conclusions. DSA is an effective method for detecting collateral circulation related to HAO and may provide information to guide transcatheter management decisions.